PALEOMAGNETIC REFERENCE INTERVALS OF THE LATE PLEISTOCENE IN THE CENTRAL AREA OF THE RUSSIAN PLAIN - Svetlitskaya T.V.; Velichko A.A. (My University, 1988)
In the Pleistocene, which is encompassed entirely by the 0.73 million years long Brunhes paleomagnetic epoch, paleomagnetic episodes such as the Blake Espisode cannot be reliably traced. As a result, efforts to improve the detail of the magnetostratigraphic scale of the Pleistocene focus on finding lower-rank fluctuations in the earth's magnetic field, i.e., excursions. No fewer than 12 excursions have been identified in the Brunhes epoch. To identify paleomagnetic anomalies and define their age, the authors investigated several sections in the zone of greatest accumulation of late Pleistocene loess-soil series in the central area of the Russian plain. The study proves the existence, in subaerial deposits of late Pleistocene loessial soil series that can subdivided in detail, of consistent paleomagnetic excursion with a reliable chronostratigraphic positions. These may be treated as magnetostratigraphic reference levels in correlating sections on the Russian plain and in adjoining areas.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен